Tradução do conhecimento em um jogo digital para promoção da autonomia feminina no processo de parto e nascimento - Honnef, Fernanda (2023)
Introduction: Childbirth, as a physiological event in a woman’s sexual and reproductive life, must be accompanied and assisted by professionals, with the aim of respecting women’s autonomy so that they can experience childbirth actively, playing a leading role. To achieve this, women need to be provided with information about the childbirth process. Objective: To create and validate the textual and visual content of a care-educational technology in the form of an interactive narrative digital game to promote access for pregnant women and their companions to information that foster good practices in childbirth. Method: Methodological study using the Knowledge to Action framework, with the development of the knowledge creation component. To create an interactive narrative digital game, the textual content was selected based on qualitative evidence from primary studies and the synthesis of recommendations on good practices in labor and childbirth. Twenty-four illustrations were applied to the content to improve understanding and engage the target audience. Content validation was carried out with a population of 15 experts. Data was collected through a Google Forms survey made available by email or WhatsApp, using the snowball sampling technique. The analysis was carried out according to the Content Validity Index (CVI), applying a Likert-type scale for relevance, pertinence and clarity of content. The ethical recommendations provided for in Resolution 510/16 were complied with. Results: The validation involved professionals from the South, Southeast and Northeast regions of Brazil. The professionals were nurses and a physiotherapist. The CVI was > 0.8, and the experts’ suggestions regarding the content and images were met. The game’s textual and visual content included information about recommended practices for labor and childbirth, such as prenatal care, birth plans, the use of non-pharmacological pain relief methods, freedom of movement, and non-recommended practices. The content was uploaded into the Twine platform for the development of the game, which is hosted on an open-access website. Conclusions: with the creation and validation of an interactive narrative digital game on the Twine platform, the result is a care-educational technology with its content based on evidence and translated to inform and promote good practices in childbirth for the target audience of pregnant women and their companions. It can be used in the context of healthcare services in the everyday routine of prenatal care as a health education method.